Studies in Effect of Synthetic and Natural Microfibers on Properties of High-Density Polyethylene-Reinforced Composite. Issue 2 (22nd January 2017) - Gaikwad, Pravin; Mahanwar, Prakash
ABSTRACT: Natural fibers are now arising as one of the promising reinforcement components for fiber-reinforced polymer composites. A study has been conducted to optimize weight concentration of surface-treated and surface-untreated microfibers on the properties of high-density polyethylene composite. Polyethylene terephthalate and henequen microfibers in varying compositions, namely, 1, 3, 5, 8, 10, and 20 wt% were reinforced into high-density polyethylene matrix. These fibers were treated with coupling agent at 0.5 wt%. Vinyltrimethoxysilane-treated composite shows enhanced properties as compared to untreated microfiber composite. Rheological and morphological results reveal that addition of coupling agent improves dispersion and matrix fiber interactions. GRAPHICAL ABSTRACT: